Compulsory Schooling in Australia Perspectives from Students, Parents, and Educators - Reid, Carol; Watson, Katherine (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
In an examination of the impact of education policy on Australia's diverse student population, this book asks if increasing the years of compulsory schooling can make the positive social impact its proponents claim. The authors' analysis reveals a policy disjuncture wrought by competing agendas of increased school leaving age and school choice.